Clinical Ethicists and Medical Assistance in Dying (MAiD): Possible Roles and Challenges - Finley-Roy, Vanessa (Bioethics, 2026)
Assisted dying (AD) presents a range of challenges for clinical ethicists (CEs) and healthcare institutions seeking to involve them in its provision. Questions regarding the legitimacy, scope, and nature of CE involvement remain underexplored in the literature. This article addresses this gap by first outlining the professional standards that guide CE practice and presenting arguments for the value of ethics expertise in AD contexts. We then examine the Canadian MAiD landscape and draw on the experiences of CEs—particularly within a healthcare institution in Quebec—to propose a typology of roles that CEs have occupied at various moments and levels throughout the emergence and institutionalization of AD. These roles span micro to macro levels of involvement and reflect both practical contributions and normative considerations. In the final section, we return to the foundational normative questions raised at the outset—not to offer definitive answers, but to contribute meaningfully to ongoing reflection about CE involvement in AD. By analyzing professional standards alongside the diverse roles CEs have played, we assess the benefits and challenges of their participation in this ethically complex domain and offer guidance for institutions seeking to engage ethics expertise in AD policy and practice.